Ratio and proportion through realistic mathematics education and pendidikan matematika realistik Indonesia approach: A systematic literature review - Risdiyanti, Irma; Zulkardi; Putri, Ratu Ilma Indra; Prahmana, Rully Charitas Indra; Nusantara, Duano Sapta (Jurnal Elemen, 2024)
Foundational mathematical concepts like ratios and proportions are indispensable for solving both everyday problems and those encountered in professional settings. However, many students need help to grasp and apply these concepts effectively, often due to ineffective teaching methods, variations in students' levels of comprehension, and shortcomings in existing learning models. Realistic Mathematics Education (RME) and Pendidikan Matematika Realistik Indonesia (PMRI) have emerged as promising solutions to address these challenges. This study aims to systematically review the literature on ratio and proportion learning design using RME and PMRI approaches. It focuses on three specific research inquiries: profiling the literature, analyzing employed learning designs, and identifying gaps and recommendations for further research in learning design development. Conducted through a Systematic Literature Review (SLR) approach, the research involved planning, implementing, and disseminating review results. One hundred forty-four documents were scrutinized, leading to the identification of 19 pertinent papers. This study provides a comprehensive analysis of the literature on learning design in the context of ratio, proportion, scale, and level, utilizing RME and PMRI approaches while highlighting research gaps and offering insights for future studies. Its findings hold significant implications for educators and researchers seeking to enhance mathematics education through RME and PMRI approaches.